(untitled) (Annals of Bangladesh Agriculture, 2019)
Processing quality of potato tubers depend on the physico-chemical properties which changes within the time in long-term storage period. The present study was conducted to find out a suitable storage condition that could be able to maintain the processing quality of potatoes. Three potato varieties namely Asterix (BARI Alu-25), Courage (BARI Alu-29) and Lady Rosetta (BARI Alu-28) and three different storage conditions viz. Bamboo chamber (BC), earthen chamber with evaporative cooler (EC) and refrigerator (RF) were used in this study. Data were recorded monthly-basis on the physico-chemical processing qualities of the potato tubers. Potato tubers stored in RF was able to maintain higher dry matter content and lower weight loss, shrinkage and energy content than BC and EC. Though the physical qualities of the refrigerated tubers were well-maintained, but produced considerably higher amount of mean reducing sugars (2.69 mg/g FW) which was 11.6 and 17.9% higher than the mean of BC (2.41 mg/g FW) and EC (2.28 mg/g FW), respectively; and higher mean sucrose contents (2.46 mg/g FW) which was 6.5 and 18.8% higher than the mean of BC (2.31 mg/g FW) and EC (2.07 mg/g FW), respectively. EC maintained significantly lower amount of mean glucose (0.17 mg/g FW), fructose (1.96 mg/g FW) and total soluble sugar (4.20 mg/g FW) contents than BC and RF. Compared to pre-storage, mean reducing sugar content was increased by 1.5, 1.7 and 2.0 times in EC, BC and RF, respectively until 90 days of storage and the increase in mean sucrose content was 1.7-, 2.1- and 2.3-fold in EC, BC and RF, respectively. Among the varieties, Courage and Lady Rosetta were suitable for long-term storage for processing than Asterix. Chips produced from the potatoes stored in the EC acquired significantly higher scores for sensory attributes than that of BC and RF. Results clearly depicted that potatoes stored in EC were more suitable for processing due to moderate retention of dry matter content (22.13%) and lower accumulation of different sugars and were able to retain processing quality up to 90 days of storage than that of BC and RF. Ann. Bangladesh Agric. (2019) 23(2) : 61-78